ITN protection, MSP1 antibody levels and malaria episodes in young children of rural Burkina Faso - Kynast-Wolf, Gisela; Wakilzadeh, Wieda; Schnitzler, Paul; Becher, Heiko; Müller, Olaf (Acta tropica, 2012)
Malaria blood-stage vaccines are in an early phase of clinical development with MSP1 being a major antigen candidate. There are limited data on the protective efficacy of antibodies against subunits of MSP1 in the malaria endemic areas of sub-Saharan Africa. This prospective cohort study was nested into a large insecticide-treated mosquito net (ITN) trial during which neonates were individually randomised to ITN protection from birth vs. protection from month six onwards in rural Burkina Faso. A sub sample of 120 children from three villages was followed for 10 months with six measurements of MSP142 antibodies (ELISA based on recombinant 42kDa fragment) and daily assessment of malaria episodes. Time to the next malaria episode was determined in relation to MSP142 antibody titres. MSP142 antibody titres were dependent on age, season, ITN-group, number of previous malaria episodes and parasitaemia. There were no significant differences in time until the next malaria episode in children with low compared to children with high MSP142 antibody titres at any point in time (101 vs. 97 days in May, p=0.6; 58 vs. 84 days in September, p=0.3; 144 vs. 161 days in March, p=0.5). The findings of this study support the short-lived nature of the humoral immune response in infants of malaria endemic areas. The study provides no evidence for antibodies against a subunit of MSP1 being protective against new malaria episodes in infants.